Optimalisasi Intellectual Capital dan Implementasi Green Accounting dalam Meningkatkan Kinerja Keuangan - Agustin, Mega Widia; Sari, Intan Rahma (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
This research aims to determine the influence of intellectual capital and green accounting on financial performance. Intellectual capital is measured by VAIC, green accounting is measured by PROPER and financial performance is measured by Return on Assets (ROA). The population in this research are all companies in the Consumer Non-Cyclicals and Energy sectors listed on the Indonesia Stock Exchange (BEI) between 2018 - 2022. The number of samples in this research was 14 companies obtained through the purposive sampling method. 70 sample data were obtained. The type of data in this research is secondary data with quantitative research methods. The analysis technique used is panel data regression analysis with a significance level of 5%. This research was processed using eviews 12 software and shows that (1) Intellectual Capital has a significant effect on financial performance, which means the hypothesis is accepted, and (2) Green Accounting has no effect on financial performance, which means the hypothesis is rejected.